Implications Of The Implementation Of Clinical Authority On Improving The Quality Of Nursing Services - Pujianti, Rosalia; Bandur, Agustinus; Dedi, Blacius (International Journal Labs, 2024)
Literature studies indicate that implementing clinical authority can enhance the quality of nursing care. However, many hospitals still have not fully applied clinical authority aligned with nurses' career paths. This research explores the impact of clinical authority on nurses' performance, both directly and indirectly, through situational leadership in Hospital X. Using a mixed-method approach with a parallel concurrent triangulation model, the study collected quantitative data via questionnaires from 300 nurses using total sampling. Descriptive crosstab analysis revealed no significant differences in perceptions of clinical authority, performance, and situational leadership based on individual characteristics. Structural Equation Modeling showed that clinical authority positively and significantly affects nurse performance. Qualitative data were gathered through focus group discussions with 13 nurses and semi-structured interviews with senior nursing managers. Thematic analysis identified six key themes: positive impacts on performance, the role of situational leadership styles, strategies to optimize nursing services, encountered obstacles, competitive challenges, and motivation to enhance care. The qualitative findings indicated that clinical authority fosters nurses' responsibility, adherence to standards, mutual trust, teamwork, and improved communication and caring attitudes. The corroboration of quantitative and qualitative analyses demonstrated alignment, confirming that clinical authority significantly influences nurse performance. To improve nursing care quality, hospitals are encouraged to implement structured career paths for nurses, ensuring that clinical authority is supported at every level